THE CORRELATION BETWEEN STUDENTS READING SPEED AND STUDENTS READING COMPREHENSION IN NARRATIVE TEXT AT THE SECOND SEMESTER OF EIGHTH GRADE OF MTsS NURUL HUDA BANJARSARI: English - Victa Suhbatur Rosadi Rosadi; Ahmad Saifudin; Tyas Alhim Mubarok (Prodi Tadris Bahasa Inggris, 2023)
The purpose of this study was to determine the relationship between students' reading speed and reading comprehension in class VIII narrative texts at MTsS Nurul Huda Banjarsari. This study presented the question,